A Solid‐State Electrochemiluminescence Sensor for Label‐Free Analysis of Leukemia Cells. Issue 7 (14th June 2013) - Liu, Afang; Qing, Meng; Pan, Yuliang; Peng, Ying; Guo, Manli; Huang, Yan; Nie, Zhou; Yao, Shouzhuo
Abstract A novel electrochemiluminescence (ECL) method for label‐free detection of cancer cells was proposed for the first time by capturing negatively charged Jurkat cells onto Ru(bpy′) <![CDATA[2+3]]> <inline-graphic xlink:href="ark:/27927/pgg2714cdvv" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />‐immobilized indium tin oxide (ITO) electrode via electrostatic interaction. The ECL sensor exhibited excellent sensitivity, good stability and a linear response to Jurkat cells in the concentration range from 1×103 to 2×105 cells/mL, with a detection limit of 730 cells/mL. Furthermore, the method was successfully applied in the study of cell growth and cell apoptosis, which was supported by fluorescent images analysis. The proposed protocol is simple, rapid, inexpensive and universally targetable for tumors, offering a novel platform for the development of an ECL biosensor for cell detection.